A perda do objeto da ação direta de inconstitucionalidade : mudança de paradigma procedimental tendo em vista a supremacia do texto constitucional - Santana, Rodrigo Freitas de (2013)
This study has the initial object of analyze the judicial review and its mode of action as a defense system of the Constitution against the normative acts that comprise the Brazilian legal system, studying their species from various criteria, as well as analyzing the competent organs for its exercise and the way it operates in the context of this defense system . This work also seeks to study in more detail the abstract control of constitutionality, analyzing the constitutional actions that integrate it, evaluating their procedures and identifying its effects, detaining with more specificity about their objects and their importance to the continuation of the trial process of the aforementioned actions. It also aims to assess how the contested object can interfere in the judgment of the Direct Action of Unconstitutionality - ADI, checking how this action operates to ensure the effectiveness of the control to which it belongs , even when its object no longer exists before its trial. This current study will demonstrate the procedural flaws that happen in the ADI process of trial when occurs the supervening loss of its object before the action judgment , as well as the reflections of this situation for the abstract control of constitutionality. Finally, it aims to demonstrate that based on the constitutional supremacy, basic justifying ground of the abstract and concrete, political or judicial review, is possible to make a change in the procedural paradigm, in order to allow that the supervening object loss of ADI before his trial does not prevent the Brazilian Constitutional Court to examine the question of unconstitutionality raised in the detriment of a normative act, and when recognized its disrespect to the constitutional text, remove its effects of the legal system , meaning a factual innovation to the procedure of the Direct Action of Unconstitutionality.